UJI ADAPTASI BERBAGAI JENIS VARIETAS SORGUM (Sorghum Bicolor L.) PADA LAHAN KERING DI DESA BOCOR KECAMATAN BULUSPESANTREN KABUPATEN KEBUMEN - Silfia, Galuh Iga; Barokah, Umi (Agros Journal of Agriculture Science, 2024)
Sorghum is one of the food crop commodities that is resistant to drought, so it has the potential to be developed on dry land. Therefore, information is needed related to new high-yielding varieties of sorghum plants that are short-lived and have high production yields so that farmers want to cultivate sorghum plants. This study aims to determine the adaptability of several varieties of sorghum on dry land in Leak Village, Buluspesantren District, Kebumen Regency. The research will be conducted on farmers' land from December 2023 to March 2024. A total of 14 varieties of sorghum from the Cereal Plant Instrument Standard Testing Center, Maros, South Sulawasi were tested in this study. Planting is carried out by planting seeds directly as much as 2-3 seeds / planting holes on plots measuring 2 m x 3 m with a planting distance of 30 cm x 50 cm. The study was arranged using RAKL with 3 repetitions. The results of the variance analysis showed that there were differences between varieties tested on plant height characters, panicle/sample weight, seed/plot weight and 50% flowering age. Different varieties of sorghum affect the growth and yield of sorghum plants in the dry land of Leaky Village, Buluspesantren District, Kebumen Regency. In varieties Super 2 and Super 1 Have the highest plant height. The short-lived varieties of sorghum are UPCA S1 and Suri 3 varieties. Varieties that have high yields are Bioguma 2 and Soper 9.